PERFORMANCE OF NEW BIVOLTINE DOUBLE HYBRIDS OF THE SILKWORM BOMBYX MMORI L. UNDER LARGE SCALE IN-HOUSE TESTING - ., DAYANANDA; RAO, P. RAMA MOHANA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
popular single hybrid CSR2 X CSR4 were reared in large scale with 200 difls each and evaluated. Data indicate that double hybrids have recorded 20-24% improvement in fecundity compared to the single hybrid component. Among the three double hybrids evaluated (D7 x S5) x (D13 x S1) is significantly superior over the other hybrids in cocoon weight (2.025 g), cocoon shell weight (0.459 g) and cocoon yield (76.328 kg/ 50,000 eggs).